2016
DOI: 10.1183/13993003.01062-2016
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in chronic pulmonary aspergillosis

Abstract: Chronic pulmonary aspergillosis (CPA) is a chronic progressive infection that destroys lung tissue in non-immunocompromised patients. Contemporary series suggest 50-85% 5-year mortality, with few prognostic factors identified.A cohort of 387 CPA patients referred to the UK's National Aspergillosis Centre from 1992 to June 2012 was studied until June 2015. The impact of objective and subjective variables including age, sex, previous pulmonary conditions, dyspnoea score, quality of life, serum albumin and C-reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
127
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(147 citation statements)
references
References 48 publications
11
127
1
8
Order By: Relevance
“…Patients with a high AGR and less severe clinical condition can move to low-level hospital to avoid over-treatment, which can effectively shorten the hospitalization time in high-level hospitals and reduce the loss of economic and social benefits. The serum albumin concentration is a prognostic factor in many lung diseases (24,25). We did not follow up on the prognosis of our patients, but early studies have shown that the AGR can be utilized to evaluate tumor prognosis (26,27).…”
Section: Discussionmentioning
confidence: 95%
“…Patients with a high AGR and less severe clinical condition can move to low-level hospital to avoid over-treatment, which can effectively shorten the hospitalization time in high-level hospitals and reduce the loss of economic and social benefits. The serum albumin concentration is a prognostic factor in many lung diseases (24,25). We did not follow up on the prognosis of our patients, but early studies have shown that the AGR can be utilized to evaluate tumor prognosis (26,27).…”
Section: Discussionmentioning
confidence: 95%
“…Chronic pulmonary aspergillosis (CPA) is an emerging global infectious disease, estimated to affect 3 million persons worldwide [1,2]. CPA also carries a high mortality and morbidity rate, with the 5-year mortality estimated to be 50e85% [3]. CPA is intertwined with TB disease, because the global TB burden remains large and prior TB is the single most important risk factor of CPA [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…It is one of several respiratory diseases caused by the ubiquitous fungal genus, Aspergillus, of which A fumigatus is the most common human pathogen. CPA occurs mainly in immunocompetent patients with underlying respiratory conditions, including chronic obstructive pulmonary disease, sarcoidosis and previous Mycobacterium tuberculosis (MTB) infection . Globally, CPA is estimated to affect half a million people, producing a significant global health concern .…”
Section: Introductionmentioning
confidence: 99%
“…Globally, CPA is estimated to affect half a million people, producing a significant global health concern . Overall, the ten‐year mortality in patients affected by CPA exceeds 50% …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation